Literature Study on Jinayah Fiqh and Sources of Islamic Criminal Law from a Sharia Perspective - Adam Muklis Sulaiman; Hamzah Irfanda; Syifa Ullinnas (Penerbit Hellow Pustaka, 2026)
Fiqh Jinayah is a branch of Islamic jurisprudence (jurisprudence) that regulates criminal acts and punishments in Islam with the aim of maintaining the safety, justice, and welfare of society. This article focuses on an in-depth examination of classical and modern literature related to the concept of criminal jurisprudence and the sources of criminal law from a sharia perspective. The method used in this research is a literature review, examining related jurisprudence books, academic books, and scholarly articles. The findings of this study indicate that the basis of criminal law in Islam is derived from the Qur'an, Sunnah, ijma', and qiyas, all of which prioritize the principles of justice, crime prevention, and the protection of human rights. It is hoped that this research will broaden academics' insight into fiqh jinayah and its relevance to current Islamic legal studies